The Effect of Balance, Arm Muscle Strength, and Creativity towards Discus skills on Faculty of Students of Manado State University Science - Tony Pandaleke; Firmansyah Dlis; Widiastuti (Britain International for Academic Research (BIAR) Publisher, 2019)
The aims of the study is to find out The Effect of Balance, Arm Muscle Strength, and Creativity towards Discus skills. This research was carried out on the campus of the Faculty of Sport Science, Manado. State University in Tondano City, Minahasa Regency. This research is a descriptive study. The result of the study is There is a positive direct effect of balance on Discus Throwing Skills at the Faculty of Sport Sciences Mando State University Students. This means that a good balance will result in increased discus throwing skills. There is a positive direct effect of arm muscle strength on discus throwing skills at the students of the Faculty of Sport Science, Mando State University. This means that good arm muscle strength will result in increased discus throwing skills achieved by the student concerned. There is a direct influence on the position of creativity fantasy on discus throwing skills at the Students of the Faculty of Sport Science, Mando State University. This means that good creativity will result in increased disc throwing skills.